Duolingo: An Alternative Application for Learning English Grammar and Vocabulary - Widodo Widayanto; Ahmad Syafii (STKIP Al Hikmah Surabaya, 2020)
This article explores about the using an already existing language learning app, Duolingo, as an alternative application for learning English grammar and vocabulary. Duolingo is a platform that provide a language-learning website and app. The app and the website are free, so everyone can use it without giving any extra fee. The aim of this application is to teach vocabulary and grammar, which some exercise series that can be chosen by the user. In this study, writer discuss about the using of Duolingo in mobile version. The writer consider that almost student in this era are using mobile phone. Hopefully by using this application, will motivate student in learning English, especially grammar and vocabulary.